Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To determine which point lies on the graph of the transformed function, we need to first understand the transformations applied to the original function [tex]\( f(x) = |x| \)[/tex].
### Step-by-Step Solution:
1. Original Function:
The original function given is [tex]\( f(x) = |x| \)[/tex].
2. Translation Left by 2 Units:
Translating a function [tex]\( f(x) \)[/tex] left by 2 units changes the function to [tex]\( f(x + 2) \)[/tex].
3. Translation Up by 1 Unit:
Translating a function [tex]\( f(x) \)[/tex] up by 1 unit changes the function to [tex]\( f(x) + 1 \)[/tex].
4. Combining the Transformations:
Apply the transformations one after the other:
- First, translate left by 2 units to get [tex]\( f(x + 2) \)[/tex].
- Then, translate up by 1 unit, which gives us [tex]\( f(x + 2) + 1 \)[/tex].
Thus, our transformed function becomes:
[tex]\[ g(x) = |x + 2| + 1 \][/tex]
5. Evaluating Each Point:
Now, we need to check which of the given points satisfies the transformed function [tex]\( g(x) = |x + 2| + 1 \)[/tex].
- For point [tex]\((-4, 2)\)[/tex]:
[tex]\[ g(-4) = |-4 + 2| + 1 = |-2| + 1 = 2 + 1 = 3 \quad (\text{not equal to } 2) \][/tex]
- For point [tex]\((-3, 1)\)[/tex]:
[tex]\[ g(-3) = |-3 + 2| + 1 = |-1| + 1 = 1 + 1 = 2 \quad (\text{not equal to } 1) \][/tex]
- For point [tex]\((-2, 5)\)[/tex]:
[tex]\[ g(-2) = |-2 + 2| + 1 = |0| + 1 = 0 + 1 = 1 \quad (\text{not equal to } 5) \][/tex]
- For point [tex]\((-1, 2)\)[/tex]:
[tex]\[ g(-1) = |-1 + 2| + 1 = |1| + 1 = 1 + 1 = 2 \quad (\text{equal to } 2) \][/tex]
6. Conclusion:
Only the point [tex]\((-1, 2)\)[/tex] satisfies the equation [tex]\( g(x) = |x + 2| + 1 \)[/tex]. Therefore, the point that lies on the new graph is:
[tex]\[ (-1, 2) \][/tex]
### Step-by-Step Solution:
1. Original Function:
The original function given is [tex]\( f(x) = |x| \)[/tex].
2. Translation Left by 2 Units:
Translating a function [tex]\( f(x) \)[/tex] left by 2 units changes the function to [tex]\( f(x + 2) \)[/tex].
3. Translation Up by 1 Unit:
Translating a function [tex]\( f(x) \)[/tex] up by 1 unit changes the function to [tex]\( f(x) + 1 \)[/tex].
4. Combining the Transformations:
Apply the transformations one after the other:
- First, translate left by 2 units to get [tex]\( f(x + 2) \)[/tex].
- Then, translate up by 1 unit, which gives us [tex]\( f(x + 2) + 1 \)[/tex].
Thus, our transformed function becomes:
[tex]\[ g(x) = |x + 2| + 1 \][/tex]
5. Evaluating Each Point:
Now, we need to check which of the given points satisfies the transformed function [tex]\( g(x) = |x + 2| + 1 \)[/tex].
- For point [tex]\((-4, 2)\)[/tex]:
[tex]\[ g(-4) = |-4 + 2| + 1 = |-2| + 1 = 2 + 1 = 3 \quad (\text{not equal to } 2) \][/tex]
- For point [tex]\((-3, 1)\)[/tex]:
[tex]\[ g(-3) = |-3 + 2| + 1 = |-1| + 1 = 1 + 1 = 2 \quad (\text{not equal to } 1) \][/tex]
- For point [tex]\((-2, 5)\)[/tex]:
[tex]\[ g(-2) = |-2 + 2| + 1 = |0| + 1 = 0 + 1 = 1 \quad (\text{not equal to } 5) \][/tex]
- For point [tex]\((-1, 2)\)[/tex]:
[tex]\[ g(-1) = |-1 + 2| + 1 = |1| + 1 = 1 + 1 = 2 \quad (\text{equal to } 2) \][/tex]
6. Conclusion:
Only the point [tex]\((-1, 2)\)[/tex] satisfies the equation [tex]\( g(x) = |x + 2| + 1 \)[/tex]. Therefore, the point that lies on the new graph is:
[tex]\[ (-1, 2) \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.